IMPACT OF TEACHER-LEARNERS RELATIONSHIP ON STUDENTS’ ACADEMIC PERFORMANCE IN BUSINESS EDUCATION IN AWKA SOUTH LOCAL GOVERNMENT AREA OF ANAMBRA STATE, NIGERIA - Dorathy Ogochukwu Anike (Indonesian Journal of Education (INJOE), 2026)
This study examined the effect of teacher-student relationship on academic performance of business education students at Awka South, Local Government Area of Anambra state. The descriptive survey research design was used and guided by three research questions. Data were gathered by a structured questionnaire from the respondents, followed by the mean and SD analysis. The study employed descriptive survey design that was administered to 200 public junior secondary students from 10 schools that were randomly selected in Awka South. There was a reliability coefficient of 0.83 using a data collection instrument that was validated according to a 15 item questionnaire. Data analysis was carried out using mean and standard deviation, and the criterion for the acceptance was 2.50. It was found that positive teacher-student relationships have a significant positive effect on Academic Achievement, because friendly teachers make students interested in the subject (Mean = 2.85) and listening to the student's opinion improves students' motivation in the classroom (Mean = 3.00). On the other hand, the lack of positive relationship creates great problems, such as high classroom anxiety (Mean = 3.20) and students not seeking help when confused (Mean = 2.93). In order to create a better classroom climate, the respondents agreed that setting up models of fair, non-threatening environments (Mean = 3.30) and providing models of interactive group projects (Mean = 3.03) are highly effective. Regular constructive feedback was not seen as one of the main factors (Mean = 2.25). The study found that supportive emotional climates play a significant role in being able to achieve the maximum success in Business Education. On this basis, it is recommended that targeted professional development opportunities for business educators be provided in order to develop a set of approaches that are accessible to students, and that institutions have clear guidelines that encourage safe, interactive, and equitable learning environments.